Emerging Concepts of Tumor Exosome–Mediated Cell-Cell Communication 2012
DOI: 10.1007/978-1-4614-3697-3_4
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Importance of Tetraspanins in Exosomes

Abstract: Exosomes are small vesicles that derive from the release of limiting membranes from multivesicular bodies (MVB). They carry and transfer selected membrane and cytoplasmic proteins, mRNA, and microRNA into target cells. Due to this shipping of information, exosomes are considered to be a most promising therapeutic tool for multiple diseases.Whereas knowledge on the composition of exosomes is rapidly increasing, the mode of selective recruitment into exosomes as well as target cell selection is poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 295 publications
(329 reference statements)
0
5
0
Order By: Relevance
“…After ultracentrifugation, the nanovesicles isolated from these OSCC cells were then characterized and showed typical morphology and markers of small EVs. The protein markers such as transmembrane tetraspanins CD9, CD63, CD81 and heat shock proteins HSC70 were used in this study to perform identity verification of the isolated vesicles and they were found to share the same characteristics as small EVs including exosomes derived from many cell types [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…After ultracentrifugation, the nanovesicles isolated from these OSCC cells were then characterized and showed typical morphology and markers of small EVs. The protein markers such as transmembrane tetraspanins CD9, CD63, CD81 and heat shock proteins HSC70 were used in this study to perform identity verification of the isolated vesicles and they were found to share the same characteristics as small EVs including exosomes derived from many cell types [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is still debate as to whether MBVs possess all of the characteristics required to be defined as an EV, there is also evidence that EVs can bind to ECM components; for example, a study by Narayanan et al showed binding of MSC-derived EVs to bind to both fibronectin and collagen type I in the ECM ( Narayanan et al, 2016 ). Such interactions between EVs and the ECM are likely mediated by adhesion receptors, known to be present on the exosomal membrane, including integrins, tetraspanins, and ICAM-1 ( Escola et al, 1998 ; Thery et al, 1999 , 2001 ; Rana and Zoller, 2013 ).…”
Section: A Bioengineering Approach To Manufacturing and Enhancing Ev mentioning
confidence: 99%
“…More specifically, the analyzed exosomal fractions were enriched in adhesion molecules such as tetraspanins (eg. CD47, CD81, CD82, and CD9) and integrins, membrane transport and fusion proteins, including annexins, flotillins, and Rabs, ESCRT, heat shock and signaling proteins, cytoskeleton and ion transport components, as well as metabolic enzymes ( Supplementary Table 2 ); all these proteins have been found, by MS/MS analysis, to comprise characteristic components of exosomes from different cell types [ 47 ], [ 48 ]. Consistently, screening of the 614 identified exosome-specific proteins with the Vesiclepedia and ExoCarta databases showed a 71 % and 76% overlap, respectively ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, proteomic analysis revealed that almost half of the identified cargo proteins were classified in the extracellular exosome GO, demonstrating a substantial overlap with known extracellular vesicle databases (Vesiclepedia, and ExoCarta), and that brain tissue was identified as the main source of their origin. Taken all together, we established that the isolated vesicular preparations meet the criteria of intact brain extracellular vesicles enriched in exosomes [ 8 , 47 , 48 ] and thus ensured that any ExE-EV-related phenotype could not be attributed to the heterogeneous starting material. Importantly, PFF injection did not alter the quantity, shape and size distribution of the isolated ExE-EVs in both WT and α-Syn KO background, in comparison to the respective controls.…”
Section: Discussionmentioning
confidence: 99%